RELATIONSHIPS BETWEEN ISLAM AND JUDAISM IN THE MODERN ERA (International Conference on Social and Islamic Studies, 2022)
This paper aims to describe the relationship between Islam and Judaism in the Modern Era. The three main points answered in this paper are; The method used is the method of writing history which includes heuristics, source criticism, interpretation and historiography. The historical method is useful for systematically and objectively reconstructing the past in order to reach a complete conclusion. The results of the study show that the relationship between Islam and Judaism in the modern era is Islam and Judaism as the nation's designation for the nation of the descendants of the Prophet Ishaq (son of the Prophet Abraham). Judaism as a religion is a divine religion broadcast by the Prophet Musa guided by the Torah. In the history of its journey, Jews developed rapidly in Israel, while Muslims developed in various regions and countries, even in its history, Islam once dominated Western power, which was able to lead the world towards high civilization and culture. Relations between Islam and Judaism were initially quite open, this was evidenced in the order of life of the people of Medina under the reign of the Prophet Muhammad. However, this did not last long because the Jews wanted to dominate by instilling influence on the Muslims, then they (the Jews) failed, and as a consequence they were expelled, so the Jews became enemies of the Muslims in various ways which are stated in the Qur'an. that they (the Jews) are very violent towards Islam.